2000
DOI: 10.1007/3-540-45140-4_29
|View full text |Cite
|
Sign up to set email alerts
|

On Structured Workflow Modelling

Abstract: Abstract. While there are many similarities between the languages of the various workflow management systems, there are also significant differences. One particular area of differences is caused by the fact that different systems impose different syntactic restrictions. In such cases, business analysts have to choose between either conforming to the language in their specifications or transforming these specifications afterwards. The latter option is preferable as this allows for a separation of concerns. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
146
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 9 publications
1
146
0
2
Order By: Relevance
“…Fig.1(b) shows a semantically equivalent yet structured model. Previous research on structured process modeling has demonstrated that not all unstructured process models can be transformed into equivalent structured models [11]. Such models are hereby called inherently unstructured.…”
Section: The Notion Of Structurednessmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig.1(b) shows a semantically equivalent yet structured model. Previous research on structured process modeling has demonstrated that not all unstructured process models can be transformed into equivalent structured models [11]. Such models are hereby called inherently unstructured.…”
Section: The Notion Of Structurednessmentioning
confidence: 99%
“…There are two root causes for process models being inherently unstructured. The first one arises from the structure shown in Fig.2; it has been shown to be inherently unstructured in [11]. The second cause is a cycle that has more than one exit point, in which case it can only be structured by introducing boolean variables to capture part of the control-flow [23] -arguably an undesirable solution in the context of process modeling.…”
Section: The Notion Of Structurednessmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper, presumes that process schemas are well-structured [16], i.e., sequences, branchings (of different semantics), and loops are specified as blocks with well-defined start and end nodes having the same gateway type. These blocks, also known as SESE (single-entry-single-exit) blocks (cf.…”
Section: Fundamentals On Time-aware Process Schemamentioning
confidence: 99%
“…The challenge in this context is to define a transformation from an unstructured model towards a structured model. It is well known that a structured model can always be constructed for process models without concurrency, but that some concurrent behaviour is inherently unstructured [52]. The research reported in [50] presents a approach based on the identification of ordering relations which leads to a maximally structured model under fully concurrent bisimulation.…”
Section: Refactoring the Structure Of Process Modelsmentioning
confidence: 99%